PELAYANAN PUBLIK DI KANTOR PERBENDAHARAAN NEGARA PROVINSI KALIMANTAN BARAT - E.21105030, Rahmat (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study is the lack of availability of forms / form SPM (Payment Order) thus impeding service to the community and stakeholders, lack of operational funds, so that employees are not proactive in providing services to the community, and the lack of operational equipment fittings, making it difficult for employees in running errands. The purpose of this study is to examine and describe the Quality of Public Services at the Regional Office of Directorate General of Treasury XVI of West Kalimantan province with a qualitative approach. The results showed that the Public Service in the Office of the Directorate General of Treasury XVI province of West Kalimantan can be quite good. It is evident from some of the interview informants who stated quite good, especially on indicators of reliability and readiness officer. Whereas on other indicators such as keberwujudan, empathy and competencies they informant who expressed less satisfaction. Addressing the phenomenon that there must be a strong commitment from all elements of the XVI Regional Office of Directorate General of Treasury, province of West Kalimantan both of subordinates to superiors to implement excellent service without receiving something in return for services provided. Furthermore expected to provide insight to the work force that XVI Regional Office Directorate General of Treasury West Kalimantan Province is a work area that is free of corruption, especially the unit formed by the new DIPA.Keywords:Â PublicÂ Service, Realibility ,Responsiveness ,Tangibility , Credibility, Competence, Empaty